Lymphocyte activation. II. Discriminating stimulation of lymphocyte subpopulations by phytomitogens and heterologous antilymphocyte sera - Janossy, G. (1972)
The mitogenic selectivity of four phytomitogens, phytohaemagglutinin (PHA), concanavalin (ConA), lentil mitogen (LM) and pokeweed mitogen (PWM), and a series of heterologous antilymphocyte sera (ALS) for mouse T and B lymphocytes has been investigated using thymidine uptake as a measure of proliferative activity. The results show that PHA, ConA and LM stimulate T but not B cells whereas PWM activates both T and B cells. Of six mitogenically active ALS, five were T cell specific and one B cell specific. Cortisone resistant (T) cells within the thymus showed a much greater response to all mitogens than unselected thymocytes. However, ConA and LM activated a considerable response in the latter population. Selective activation of T and B cells by aspecific means may be useful both as a clinical tool and as an approach to gaining an understanding of antigen induction of immune responses.